A New Cadmium(II) 2,6-Naphthalene dicarboxylic Acid Three-Dimensional Metal-Organic Frameworks with 6-Connected PCU Topology - Xie, Si-Cai (Asian Journal of Chemistry, 2013)
A novel three-dimensional (3D) Cd(II) metal-organic frameworks [Cd3(2,6-ntd)3(DMA)4] (1; 2,6-ntd = 2,6-naphthalene dicarboxylic acid; DMA = N,N'-dimethyl acetamide) has been solvothermally synthesized. Single-crystal structure analysis reveals that this compound crystallized in a monoclinic space group of C2/c with a = 14.4124(4) Å, b = 18.5328(4) Å, c = 21.3181(5) Å, a = 90.00º, b = 98.811(2)º, l = 90.00º, V = 5626.9(2) Å3 and Z = 4. From the viewpoint of topology, it can be reduced to a 6-connected PCU topological network.